Exploring the culture of faculty development: Insights from Canadian leaders of faculty development - Lewis, Lerona Dana; Steinert, Yvonne (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2023)
Background: Although the word culture is frequently mentioned in research on faculty development (FD), the concept is rarely explored. This research aimed to examine the culture of FD in Canada, through the eyes of leaders of FD in the health professions. Studying culture can help reveal the practices and implicit systems of beliefs and values that, when made explicit, could enhance programming.Method: FD leaders from all Canadian medical schools were invited to participate in semi-structured telephone interviews between November 2016 and March 2017. The researchers used a constructivist methodology and theoretical framework located within cultural studies, borrowing from phenomenological inquiry to move beyond descriptions to interpretations of participants’ perceptions. Constant comparison was used to conduct a thematic analysis within and across participants’ interview transcripts.Results: Fifteen FD leaders, representing 88% of medical schools (15/17) in Canada, participated in this study. Four themes characterized the culture of FD: balancing competing voices and priorities; cultivating relationships and networks; promoting active, practice-based learning; and negotiating recognition.Conclusion: Although the culture of FD may vary from context to context, this study revealed shared values, practices, and beliefs, focused on the continuous improvement of individual and collective abilities and the attainment of excellence.